The Effect of Work Card Media Integrated with the Group Investigation (GI) Cooperative Learning Model on Students' Learning Outcomes Improvement in the Colloidal System Topic - Silvia Elastari Matondang; Putri Junita Sari Nst (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to determine the improvement of learning outcomes by using work card media in the GI (Group Investigation) type cooperative learning model on colloidal system material at Al-Hidayah Medan Private High School. The population used in this study were all students of class XI IPA Al-Hidayah Medan Private High School consisting of two classes. The research sample was randomly sampled from both classes, namely the experimental class I was given GI (Group Investigation) treatment with work card media and the experimental class II was given GI (Group Investigation) treatment without work card media. The improvement of student learning outcomes was calculated using the normalized gain form and the percentage of student learning success in the experimental class I was 80.2% while the percentage of student learning success in the experimental class II was 52.1%. The hypothesis test was conducted using the right-hand t-test and obtained thitung which was 3.124 while ttabel was 1.670 for α = 0.05 and db = 61. Thus thitung > ttabel, then Ha was accepted, namely the improvement in chemistry learning outcomes by using work card media in cooperative learning type GI (Group Investigation) was better than without using work card media in the application of the cooperative learning model type GI (Group Investigation).